2021
DOI: 10.3389/fonc.2020.607840
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Low-Frequency KRAS Mutations in cfDNA From EGFR-Mutated NSCLC Patients After First-Line EGFR Tyrosine Kinase Inhibitors

Abstract: BackgroundMolecular profiling of advanced EGFR mutated NSCLC has recently demonstrated the co-existence of multiple genetic alterations. Specifically, co-existing KRAS-mutations in EGFR NSCLCs have been described, despite their prevalence at progression and their role in the response to EGFR tyrosine kinase inhibitors (TKIs) remain marginally explored. Aim of our study was to investigate the prevalence of co-existing KRAS mutations at the time of progressive disease and explore their impact on clinical outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The percentage of KRAS mutant alleles detected in the resistant tumours ranged from 0.4% to 17% [19]. Aside from that, KRAS mutations have been designated to be a driver mutation in cancer, with several publications demonstrating a low allelic frequency of KRAS concomitantly existing alongside other driver mutations such as EGFR [20,21], and it was found that de novo KRAS G12C mutation was present ranging from 0.2% [22] to 1.17% of detected samples (n = 6) [23,24]. Detecting de novo KRAS mutation requires high sensitivity and specificity technology, and it was found that KRAS mutation was absent using droplet digital PCR.…”
Section: Intrinsic Resistance In Krasmentioning
confidence: 99%
“…The percentage of KRAS mutant alleles detected in the resistant tumours ranged from 0.4% to 17% [19]. Aside from that, KRAS mutations have been designated to be a driver mutation in cancer, with several publications demonstrating a low allelic frequency of KRAS concomitantly existing alongside other driver mutations such as EGFR [20,21], and it was found that de novo KRAS G12C mutation was present ranging from 0.2% [22] to 1.17% of detected samples (n = 6) [23,24]. Detecting de novo KRAS mutation requires high sensitivity and specificity technology, and it was found that KRAS mutation was absent using droplet digital PCR.…”
Section: Intrinsic Resistance In Krasmentioning
confidence: 99%
“…Of note, a KRAS mutation is a negative predictor of response to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs; e.g., cetuximab, gefitinib, or erlotinib) (Table 2) [33][34][35][36], but a positive predictor of response to immune checkpoint inhibitors (ICIs; including anti-PD-1 and anti-PD-L1) (Table 3) [37][38][39]. However, response rates are variable and dissenting reports suggest that KRAS mutations cannot guide the therapeutic choice between TKIs and ICIs in NSCLC patients [40,41]. In PDAC, patients with KRAS-G12D mutations (but not total KRAS mutations) have a worse prognosis than patients with wild-type KRAS [42][43][44].…”
Section: Prognostic and Predictive Value Of Kras Mutationsmentioning
confidence: 99%
“…Notably, their PFS was significantly shorter compared to EGFR mutations (2.42 months vs. 11.09 months; p = 0.0081), and also the ORR was poorer (16.7% vs. 57.1%). Additionally, Nardo et al analyzed the prevalence of concurrent KRAS mutations on 106 patients with EGFR-mutant NSCLC focusing on their impact on clinical outcome [32]. Indeed, KRAS co-alterations were detected in 3 patients with a VAF of less than 0.2%, which showed poor clinical outcome to first-line EGFR-TKI, in terms of time to treatment failure (TTF), OS and PFS (five, six and five months, respectively).…”
Section: Krasmentioning
confidence: 99%